(untitled) (Global Journal of Science Frontier Research, 2023)
Mathematics has applications in every aspect of real life So many such type of real-life problems are modeled by differential equations Therefore differential equations are used as tools to solve many complex situations With the help of differential equations we can find the formula to solve many significant issues in many areas of the Anatomy and Physiology of the human body like physical mental physical and medical principles Differential equations can be linear nonlinear autonomous or non-autonomous Practically most of the differential equations involving physical phenomena are nonlinear Hence nonlinear differential equations play a vital role in case of science and engineering Nonlinear systems are differently classified and the nonlinear jerk oscillator is one of the most essential parts of a nonlinear system Different types of nonlinear jerk oscillators will be analyzed using Extended Iteration Method and the outcome may leave an impact to be better than the current results The principal advantage of this method is that it paves a suitable and smooth way and is more accurate practical easy and straightforward